Evaluation of Learning Management in Madrasahs Based on the Merdeka Curriculum - Oktavia, Anita (CV. Tripe Konsultan, 2024)
This study aims to evaluate the effectiveness of learning management in madrasahs implementing the Merdeka Curriculum. The main focus of the research is to assess the planning, implementation, and evaluation of learning conducted by educators and madrasah managers in order to improve the quality of Islamic education. This research uses literature review methods and analyzes various relevant sources, such as books, magazines, articles, and previous studies related to the Evaluation of Learning Management in Madrasahs Based on the Merdeka Curriculum. The findings show that the implementation of learning management based on the Merdeka Curriculum in madrasahs has great potential in improving the quality of Islamic education in Indonesia. However, the effectiveness of its implementation highly depends on the readiness of human resources, infrastructure, and support from the government and other education stakeholders. To achieve a more optimal implementation, strengthening teacher training, providing supporting facilities, and establishing a more structured evaluation system are necessary. The evaluation of learning management in madrasahs based on the Merdeka Curriculum is an important step in ensuring that the educational process applied is not only relevant to the needs of the times but also maintains the Islamic values that characterize madrasahs. Through improvements and strengthening of the learning management system, madrasahs are expected to become leading educational institutions in shaping a generation that is knowledgeable, has good character, and is highly competitive.